Maximum Stiffness Beam-Columns - Karihaloo, B.L. (Engineering Transactions, 1981)
The problem considered is that of maximising the flexural stiffness of a simply supported elastic bar of given length and volume which is acted upon simultaneously by an axial compression and a transverse uniformly distributed force. The cross-section of the bar is of either sandwich or solid construction. Simple formulas are presented to calculate the, minimum midspan deflection for prescribed axial compression and transverse force. It is shown that by maximising the flexural stiffness of the bar its Iateral deflection can be substantially decreased.